A highly enantioselective synthesis of the odorant, 3-hydroxy-4-phenylbutan-2-one. (28th February 2013) - Liang, Sen; Sun, Bao-guo; Tian, Hong-Yu; Wang, Ya-ling; Sun, Yu-mei
An efficient and highly enantioselective synthesis of 3-hydroxy-4-phenylbutan-2-one was developed involving the asymmetric epoxidation of an enone and hydrogenolysis of an α, β-epoxyketone. 1-Phenyl-3-buten-2-one was epoxidised with t-butyl hydroperoxide using a chiral La-BINOL-Ph3P=O complex as the catalyst to give (3S, 4R)- or (3R, 4S)-3, 4-epoxy-4-phenylbutan-2-one in ∼90% yield and 97% ee. The resultant optically active epoxyketone was reduced in the presence of Pd/C (5 mol%) and H2 (3 bar) in THF at room temperature to produce (S)- or (R)-3-hydroxy-4-phenylbutan-2-one in ∼80% yield with more than 90% enantiomeric excess.